Rekultywacja leśna realizowana na terenach pogórniczych Kopalni Siarki "Osiek" = Reclamation to forest conducted on post-mining areas lands of the "Osiek" Sulfur Mine - Pająk, Marek; Krzaklewski, Wojciech; Pietrzykowski, Marcin; Likus, Justyna; Kowalczewski, Wojciech (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The studies on the assessment of forest reclamation on post-mining areas of the Osiek Sulpfur Mine were carried out on 24 experimental plots (10 × 10 m), sixteen of which were located in the area where the full cycle of reclamation treatments was conducted, whereas eight of them were the lands where the existing secondary biocenoses were used. The ongoing forest reclamation on the post-mining lands of the "Osiek" Sulphur Mine was assessed as generally appropriate.
Keywords: rekultywacja; tereny pogórnicze; sukcesja; zalesienia; reclamation; post-mining landscape; afforestation; succession